Method of Microelektronic Charge Converter’s Sensitivity Enlargement - Sakalauskas, S.; Vaitonis, Z.; Pūras, R. (Elektronika ir Elektrotechnika, 2005)
Various methods are used for investigation and control of materials’ surface including capacitic method. The paper deals with high spatial resolution microelectronic charge converter’s sensitivity study. The sensitivity is determined by diameter of converter’s tip and parameters of primary high input resistance voltage amplifier. The analysis of electric diagrams of capacitic converter and high input resistance primary voltage amplifier disclosed that sensitivity enlargement is possible only by reducing amplifier’s input stray capacitance. That is why primary voltage amplifier’s input stray capacitance electrical compensation was suggested. The results of experiments demonstrated the reduction of amplifier’s input capacitance by factor about 100 in case of optimal compensation and the enlargement of microelectronic charge converter’s sensitivity by factor close to 10. Sensitivity reached 1 mV in the case of 1μm vibrating microelectrode tip diameter. Ill. 3, bibl. 6 (in Lithuanian; summaries in Lithuanian, English, Russian).